The meaning of the concept of love in philosophy of Friedrich Nietzsche - Gał, Ada (Hybris, 2018)
This paper presents the meaning of the concept of love in philosophy of Friedrich Nietzsche. Love in its proper form is a kind of intoxication (Rausch), therefore it is an expression of feeling of power. Besides there are also distorted types of love. There are love of the herd, which is one of the modest virtue, and Christian love as manifestation of the greatness weakness. The main aim of this paper is to demonstrate, that despite of relatively few fragments of Nietzsche’s works about love, love in his philosophy is an important component of reality. This applies especially to perfect love, which is manifestation of the being itself in its greatest fullness.